Political Budget Cycle on The Regional Elections in Indonesia - Rizqiyati, Chanif; Setiawan, Doddy (Universitas Pendidikan Indonesia, 2021)
This research aims to examine the Political Budget Cycle on The Regional Elections in Indonesia especially in Java and to give evidence related between the central government transfer and the political budget cycle authority in regions. The number of samples taken was 337 observation data during three observation periods i.e. elections years, one year before the elections, and two years before 2018, 2017, and 2015 elections. The technique of testing data used regression analysis with Eviews Software. The results of this research show that the regional elections improve grant expenditures and social aid expenditures, while investment expenditures are increased two years before the elections are held. The assumption that the incumbent candidates utilize their authority to do politicization budgets cannot be proven in this research. Besides, the relationship between the central transfer and the political budget cycle in regions cannot be proven either.